2016
DOI: 10.1055/s-0042-110851
|View full text |Cite
|
Sign up to set email alerts
|

Validierung einer deutschsprachigen Fassung des Body Checking Questionnaire (BCQ) an Jugendlichen mit Anorexia und Bulimia Nervosa

Abstract: Body-related checking behavior, as a behavioral manifestation of a disturbed body image, fosters the development and maintenance of eating disorders. The Body Checking Questionnaire (BCQ) is the most commonly used questionnaire for measuring body-related checking behavior internationally. To date, validation studies are only available for adult populations. Therefore, the aim of this study was to statistically test the German-language version of the BCQ in adolescents. A total of N=129 female adolescents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
2
6
0
2
Order By: Relevance
“…Additional analyses supported the criterion-related validity of both questionnaires in relation to a variety of criterion measures. More specifically, findings showed that the G-factors from both questionnaires were highly correlated (positively or negatively) with the criterion measures in a direction that matched the results from previous studies (Calugi et al, 2006; Campana et al, 2013; Kachani et al, 2013; Reas et al, 2002, 2006, 2009; Steinfeld et al, 2017; Vocks et al, 2008). Additionally, moderate correlations were found for the S-factors of the BCQ and BCCS and criterion measures.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Additional analyses supported the criterion-related validity of both questionnaires in relation to a variety of criterion measures. More specifically, findings showed that the G-factors from both questionnaires were highly correlated (positively or negatively) with the criterion measures in a direction that matched the results from previous studies (Calugi et al, 2006; Campana et al, 2013; Kachani et al, 2013; Reas et al, 2002, 2006, 2009; Steinfeld et al, 2017; Vocks et al, 2008). Additionally, moderate correlations were found for the S-factors of the BCQ and BCCS and criterion measures.…”
Section: Discussionsupporting
confidence: 84%
“…The results from these studies replicated the higher order CFA structure of the BCQ in samples of adolescents and/or adults. Additionally, several studies also supported the convergent validity of the BCQ factors with the BCCS factors (Haase, Mountford, & Waller, 2007; Mountford et al, 2006), and with measures of ED or DEAB (Calugi et al, 2006; Mountford, Haase, & Waller, 2007; Reas et al, 2009; Reas, White, & Grilo, 2006; Steinfeld et al, 2017; Vocks et al, 2008), body uneasiness (Calugi et al, 2006), body image avoidance (Calugi et al, 2006; Campana et al, 2013), social anxiety (Campana et al, 2013), social physique anxiety (Haase et al, 2007), depression (Steinfeld et al, 2017), and self-esteem (Steinfeld et al, 2017).…”
Section: Validation In Other Languagesmentioning
confidence: 89%
See 2 more Smart Citations
“…Weiterhin zeichnen Essstörungen sich durch Kontrollverhaltensweisen, wie z. B. Ordnungsliebe, Perfektionismus und Vermeidung von Risiken [28] aus, die ebenfalls mit anderen psychischen Störungen, wie der Zwangsstörung, Panikstörung, Agoraphobie und sozialen Angststörung assoziiert sein können [29]. Demgemäß berichten viele Studien Prävalenzen von bis zu 65 % für komorbide neurotische, Belastungs-und somatoforme Störungen bei Essstörungen.…”
Section: Häufigkeiten Psychischer Komorbiditätenunclassified